Negative electrode material and surface modification method and application thereof
By controlling the content of hydrogen, nitrogen, sulfur, and oxygen elements in the negative electrode material and using aromatic lithium compounds to generate an SEI film, the problem of active lithium loss caused by surface groups of the negative electrode material is solved, thereby improving the energy density and cycle performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411280534.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The surface groups of existing lithium-ion battery anode materials affect battery performance. In particular, graphite and silicon-carbon materials suffer severe loss of active lithium during the first charge and discharge process, resulting in decreased energy density and structural instability.
By controlling the content of hydrogen, nitrogen, sulfur and oxygen elements in the negative electrode material, and by using aromatic lithium compounds to mix with the negative electrode material precursor in an inert gas atmosphere, free lithium ions are generated to form a SEI-like film, thereby optimizing battery performance.
It improves the initial coulombic efficiency and cycle performance of the anode material, reduces active lithium loss, and enhances the energy density and structural stability of the battery.
Smart Images

Figure FDA0005042659100000011 
Figure FDA0005042659100000012 
Figure FDA0005042659100000013
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery materials, and in particular relates to a negative electrode material and a surface modification method and application thereof. Background Art
[0002] With the research and development of lithium-ion batteries, due to their various advantages, they have had a profound impact on many industries, such as the new energy vehicle industry, energy storage systems, portable electronic devices, aerospace, unmanned equipment, power tools and household appliances, wearable devices, etc. Therefore, the research on lithium-ion batteries can not only promote the progress of related technologies, but also have important strategic significance for energy consumption patterns and environmental protection.
[0003] The negative electrode material directly affects the performance of lithium-ion batteries. This is mainly because in lithium-ion batteries, the negative electrode material is the embedding and de-embedding site of lithium ions. It is responsible for storing and releasing energy, while ensuring the electron flow and structural stability of the battery during the charging and discharging process. The performance of the negative electrode material directly affects the energy density, cycle life, safety and cost-effectiveness of the battery.
[0004] Graphite and silicon carbon are the most important negative electrode materials for lithium-ion batteries. In the prior art, graphite is mainly divided into natural graphite and artificial graphite, but there are a large number of groups on the surface of both materials. These groups will be reduced by active lithium during the first charge and discharge of lithium-ion batteries, thereby reducing the active lithium content and reducing the battery energy density. The production of graphite materials requires high-temperature treatment, so the generation of surface groups is unavoidable. In addition, graphite has a special layered structure. If the method of eliminating surface groups is too drastic and destroys the layered structure, the graphite will lose its lithium storage function. As for silicon carbon, the first-week coulomb efficiency of silicon carbon material is low, generally between 80-88%, and a large amount of active lithium will be lost in the first week of charge and discharge. In addition, the volume expansion of silicon carbon material is large during the first week of charge and discharge, which makes the pole piece easy to lose powder or crack. Summary of the invention
[0005] In order to remove the surface groups of the negative electrode material while maintaining the normal performance of the negative electrode material, the present application provides a negative electrode material and a surface modification method and application thereof.
[0006] In a first aspect of the present application, a negative electrode material is provided, in which the hydrogen content is not higher than 0.2%, the nitrogen content is not higher than 0.05%, the sulfur content is not higher than 0.02%, and the oxygen content is not higher than 0.03%. The present invention can optimize the initial efficiency, energy density, and cycle performance of the battery by regulating the content of the hydrogen, nitrogen, sulfur, and oxygen elements in the negative electrode material.
[0007] According to a second aspect of the present application, a surface modification method for a negative electrode material is provided, and the surface modification method comprises the following steps: S1. In an inert gas atmosphere, a negative electrode material precursor is mixed with a first reaction liquid to obtain a first reactant; wherein the first reaction liquid comprises an aromatic lithium compound; S2. The first reactant is washed with a second reaction liquid, and after drying, a negative electrode material is obtained; wherein, in S1, the amount of the aromatic lithium compound is M mol, the amount of the negative electrode material precursor is W g, the specific capacity of the negative electrode material precursor is C mAh / g, and the amount of the aromatic lithium compound and the negative electrode material precursor satisfies the following relationship: M=W×C×γ; wherein,
[0008] The present application can regulate the reduction ability of the aromatic lithium compound by adjusting the mass ratio of the negative electrode material precursor to the amount of substance of the aromatic lithium compound, and then utilize the aromatic lithium compound to only eliminate the surface groups of the negative electrode material precursor, but will not damage the structure of the negative electrode material precursor, and allow a small amount of lithium ions to enter the interior of the negative electrode material precursor. In addition, after the negative electrode material precursor undergoes a reduction reaction in step S1, an aromatic lithium compound will remain on its surface. When the second reaction solution is added for cleaning, it will react with the residual aromatic lithium compound to generate free lithium ions. The free lithium ions formed will react with the solvent molecules to change the electron cloud structure of the solvent molecules, so that they are reduced and decomposed on the surface of the negative electrode material precursor, forming a substance similar to the SEI film on the surface of the negative electrode material precursor, thereby further improving the first-week coulomb efficiency of the negative electrode material.
[0009] Preferably, the precursor of the negative electrode material is graphite, and the specific capacity C of graphite is (C) Meet: 340mAh / g≤C (C) ≤355mAh / g.
[0010] Preferably, in S1, the volume of the first reaction liquid is V (C) L, satisfies the following relationship: V (c) =2×W×λ; where
[0011] Preferably, the precursor of the negative electrode material is a silicon-carbon material, and the specific capacity C of the silicon-carbon material is (Si) Meet: 400mAh / g≤C (Si)≤2000mAh / g. For example, the specific capacity of silicon-carbon material is 400mAh / g, 450mAh / g, 650mAh / g, 1000mAh / g, 1500mAh / g, 1800mAh / g or 2000mAh / g, etc. For silicon-carbon negative electrode materials, aromatic lithium compounds will react with silicon and carbon, but even for the purpose of removing the silicon-carbon material, it is difficult to estimate the amount of aromatic lithium compounds required by the silicon content or carbon content in the silicon-carbon material. The inventors have found through experimental summary that by utilizing the specific capacity of silicon-carbon materials (the specific capacity can be known when purchasing silicon-carbon materials), the required silicon-carbon materials and the content of aromatic lithium compounds can be quickly calculated. After surface treatment of the silicon-carbon material, the surface defects and active groups of the silicon-carbon material can be removed, the loss of active lithium can be reduced, and the first coulomb efficiency of the silicon-carbon material can be significantly improved. Furthermore, through the surface modification method provided in the present application, a small amount of active lithium will enter the material, causing the silicon-carbon material to expand prematurely, and a film will be produced on the surface of the silicon-carbon material during subsequent washing, thereby playing a certain role in inhibiting the expansion of silicon-carbon, thereby reducing the impact on the electrode.
[0012] Preferably, in S1, the volume of the first reaction liquid is V (Si) L, satisfies the following relationship: V (Si) =W×λ; where Similarly, the inventors have found through experiments that the required volume of the first reaction liquid can be quickly calculated using the above formula.
[0013] Preferably, the first reaction liquid is prepared by mixing aromatic hydrocarbons, a lithium source, and a solvent, and the aromatic hydrocarbons include at least one of biphenyl and its derivatives, naphthalene and its derivatives, pyrene and its derivatives, and diphenylmethane.
[0014] Preferably, the aromatic hydrocarbon includes at least one of naphthalene, biphenyl, 2-methylbiphenyl, 3,3'-dimethylbiphenyl, 4,4'-dimethylbiphenyl, and 3,3',4,4'-tetramethylbiphenyl.
[0015] Preferably, the solvent comprises at least one of tetrahydrofuran, 2-methyltetrahydrofuran, pentahydrofuran, hexahydrofuran, tetrahydropyran, 3-methyltetrahydropyran, and 2,3-dichlorotetrahydropyran.
[0016] Preferably, the second reaction liquid includes at least one of 2-methyltetrahydrofuran, tetrahydropyran, pentahydrofuran and hexahydrofuran.
[0017] Preferably, the second reaction liquid comprises 2-methyltetrahydrofuran and tetrahydropyran, and the volume ratio of 2-methyltetrahydrofuran:tetrahydropyran is 1-2:1-2.
[0018] Preferably, the mass ratio of the negative electrode material precursor to the amount of the aromatic lithium compound is 1 g: 0.00010-0.00750 mol.
[0019] Preferably, the ratio of the mass of graphite to the amount of the aromatic lithium compound is 1 g: 0.001270 to 0.001325 mol.
[0020] Preferably, the mass ratio of the silicon-carbon material to the amount of the aromatic lithium compound is 1 g: 0.001493-0.007465 mol.
[0021] Preferably, in S1, the negative electrode material precursor and the first reaction liquid are mixed and reacted under an inert gas atmosphere, the reaction temperature is 25 to 35° C., and the reaction time is 0.5 to 2 hours.
[0022] Preferably, in S2, the mass ratio of the first reactant to the volume of the second reaction liquid is 500g:1.5-2L.
[0023] Preferably, in S2, the step of washing treatment is: after the first reactant and the second reaction liquid are mixed, they are stirred at 30-50°C for 0.5-2 hours at a rotation speed of 500-200 rpm.
[0024] Preferably, in S2, the number of cleaning processes is not less than two times.
[0025] The third aspect of the present application provides a battery, which includes the above-mentioned negative electrode material. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0027] Example 1
[0028] In this embodiment, the negative electrode material is prepared by the following method:
[0029] S1. 30.85 g of biphenyl, 1.39 g of metallic lithium, and 1 L of 2-methyltetrahydrofuran were mixed to obtain a first reaction solution; then, under argon protection, 500 g of graphite (C = 345 mAh / g) and 42 L of the first reaction solution (the concentration unit of the first reaction solution refers to the content of the aromatic lithium compound, so that the mass of graphite and the amount of substance of the aromatic lithium compound, the mass of graphite and the amount of substance of the aromatic lithium compound satisfy the following relationship: M = W × C × γ; wherein, ), then reacting at a temperature of 25 to 35° C. and a rotation speed of 100 to 200 rpm, and filtering and separating to obtain a first reactant;
[0030] S2. According to the volume ratio, the second reaction solution is prepared with 2-methyltetrahydrofuran:tetrahydropyran = 2:1; then the first reactant obtained by the reaction and 2L of the second reaction solution are stirred at 40°C at a rotation speed of 50-200rpm for 1 hour, and the liquid is filtered and the above-mentioned washing step is repeated once; after filtering, the solid is vacuum dried to obtain a negative electrode material.
[0031] In this embodiment, the negative electrode and the battery are prepared by the following method:
[0032] Negative electrode: The negative electrode material, conductive carbon (SP), and binder (SBR) prepared above are added into deionized water at a ratio of 93:2:5 to prepare a slurry, the slurry is coated on a copper foil, and the negative electrode is obtained after drying.
[0033] Battery: Add lithium iron phosphate positive electrode material, conductive carbon (SP), and binder (PVDF) into NMP in a ratio of 92:3:5 to make a slurry, apply the slurry on aluminum foil, and obtain the positive electrode after drying; then assemble the positive electrode / negative electrode into a soft-pack battery.
[0034] Example 2
[0035] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode materials, this embodiment uses 500g of graphite with a capacity of C=355mAh / g as the negative electrode material precursor, and the mass of the graphite and the amount of the aromatic lithium compound satisfy the following relationship: M=W×C×γ; wherein, Except for the above differences, the operation steps for preparing the negative electrode material in this embodiment are strictly consistent with those in Example 1.
[0036] Example 3
[0037] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode materials, this embodiment uses 500g of graphite with a capacity of C=340mAh / g as the negative electrode material precursor, and the mass of graphite and the amount of the substance of the aromatic lithium compound satisfy the following relationship: M=W×C×γ; wherein, Except for the above differences, the operation steps for preparing the negative electrode material in this embodiment are strictly consistent with those in Example 1.
[0038] Example 4
[0039] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode material, this embodiment uses 500g of silicon-carbon material with a capacity of C=450mAh / g as the negative electrode material precursor. Specifically, step S1 is: 500g of 450mAh / g silicon-carbon material and 21L 0.0125mol / L first reaction solution (the mass of the silicon-carbon material and the amount of the aromatic lithium compound satisfy the following relationship: M=W×C×γ; wherein, ). Except for the above differences, the operation steps for preparing the negative electrode material in this embodiment are strictly consistent with those in Example 1. In this embodiment, the method for preparing the negative electrode and the battery is:
[0040] Negative electrode: The negative electrode material, conductive carbon (SP), and binder (SBR) prepared above are added into deionized water at a ratio of 90:5:5 to prepare a slurry, the slurry is coated on a copper foil, and the negative electrode is obtained after drying.
[0041] Battery: NCM ternary positive electrode material, conductive carbon (SP), and binder (PVDF) are added to NMP in a ratio of 92:3:5 to make a slurry, the slurry is coated on aluminum foil, and the positive electrode is obtained after drying; the positive electrode / negative electrode is then assembled into a soft-pack battery.
[0042] Example 5
[0043] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 4. The difference from Example 4 is that when preparing the negative electrode material, this embodiment uses 500g of silicon-carbon material with a capacity of C=1800mAh / g as the negative electrode material precursor. Specifically, step S1 is: mixing 1800mAh / g of silicon-carbon material with 21L of 0.05mol / L first reaction solution (the mass of the silicon-carbon material and the amount of the aromatic lithium compound satisfy the following relationship: M=W×C×γ; wherein, ). Except for the above differences, the operation steps of preparing the negative electrode material, the negative electrode and the battery in this embodiment are strictly consistent with those in Example 4.
[0044] Example 6
[0045] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 5. The difference from Example 5 is that when preparing the negative electrode material, this embodiment uses 500g of silicon-carbon material with a capacity of C=1800mAh / g as the negative electrode material precursor. Specifically, step S1 is: mixing 1800mAh / g of silicon-carbon material with 25L of 0.042mol / L first reaction solution (the volume of the aromatic lithium compound does not satisfy the following relationship: V (Si) =W×λ; where ). Except for the above differences, the operation steps of preparing the negative electrode material, the negative electrode and the battery in this embodiment are strictly consistent with those in Example 5.
[0046] Example 7
[0047] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 5. The difference from Example 5 is that when preparing the negative electrode materials in this embodiment, in step S2, the second reaction solution is prepared in a volume ratio of 2-methyltetrahydrofuran:tetrahydropyran=1:2. Except for the above differences, the operation steps of preparing the negative electrode materials, negative electrodes and batteries in this embodiment are strictly consistent with those in Example 5.
[0048] Example 8
[0049] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 5. The difference from Example 5 is that when preparing the negative electrode materials in this embodiment, in step S2, the second reaction solution is prepared in a volume ratio of 2-methyltetrahydrofuran:tetrahydropyran=4:1. Except for the above differences, the operation steps for preparing the negative electrode materials, negative electrodes and batteries in this embodiment are strictly consistent with those in Example 5.
[0050] Example 9
[0051] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 5. The difference from Example 5 is that when preparing the negative electrode materials in this embodiment, in step S2, only 2-methyltetrahydrofuran is used to prepare the second reaction solution. Except for the above differences, the operation steps for preparing the negative electrode materials, negative electrodes and batteries in this embodiment are strictly consistent with those in Example 5.
[0052] Example 10
[0053] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 5. The difference from Example 5 is that when preparing the negative electrode materials in this embodiment, in step S2, only tetrahydropyran is used to prepare the second reaction solution. Except for the above differences, the operation steps for preparing the negative electrode materials, negative electrodes and batteries in this embodiment are strictly consistent with those in Example 5.
[0054] Embodiment 11
[0055] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 5. The difference from Example 5 is that this embodiment does not perform step S2 when preparing negative electrode materials. Except for the above differences, the operation steps for preparing negative electrode materials, negative electrodes and batteries in this embodiment are strictly consistent with those in Example 5.
[0056] Comparative Example 1
[0057] This embodiment prepares negative electrode materials, negative electrodes and batteries with reference to the formula and method provided in Example 5. The difference from Example 5 is that when preparing the negative electrode materials, this embodiment uses 500g of silicon-carbon material with a capacity of C=1800mAh / g as the negative electrode material precursor. Specifically, step S1 is: mixing 1800mAh / g of silicon-carbon material with 21L of 0.07mol / L of the first reaction solution (the mass of the silicon-carbon material and the amount of the aromatic lithium compound do not satisfy the following relationship: M=W×C×γ). Except for the above differences, the operation steps of preparing the negative electrode materials, negative electrodes and batteries in this embodiment are strictly consistent with those in Example 5.
[0058] Comparative Example 2
[0059] This comparative example prepares the negative electrode and the battery by referring to the formula and method provided in Example 1. The difference from Example 1 is that this comparative example does not perform any treatment on the graphite. Except for the above difference, the operation steps for preparing the negative electrode and the battery in this comparative example are strictly consistent with those in Example 1.
[0060] Comparative Example 3
[0061] This comparative example prepares the negative electrode and the battery with reference to the formula and method provided in Example 5. The difference from Example 5 is that this comparative example does not perform any treatment on the silicon-carbon material (C=1800mAh / g). Except for the above difference, the operation steps for preparing the negative electrode and the battery in this comparative example are strictly consistent with those in Example 5.
[0062] Test Case
[0063] 1. Test subjects
[0064] Examples 1 to 10 are negative electrode materials prepared in Comparative Examples 1 to 4 and batteries using the same.
[0065] 2. Test Method
[0066] (1) First-week coulombic efficiency (first efficiency): The first charge capacity and first discharge capacity of the battery are measured using a current density of 0.2C. The first-week coulombic efficiency is calculated as follows: (first charge capacity / first discharge capacity)*100%.
[0067] (2) Energy density: For ternary material batteries, the energy density is calculated as follows: first discharge capacity*3.6V / battery weight; for lithium iron phosphate batteries, the energy density is calculated as follows: first discharge capacity**3.2V / battery weight.
[0068] (3) Cycle performance: The battery was charged and discharged cyclically at room temperature using a current density of 1C, and the battery capacity retention rate after 1000 cycles was compared.
[0069] (4) Test of element content on the surface of negative electrode materials: Take 5-30 mg of the powder test object, ensure that the sample is non-magnetic, non-corrosive, and has no volatile elements, and the length, width, and height do not exceed 5*5*3 mm; then use double-sided tape (ordinary / conductive tape) to stick it directly on the sample table; transfer the test object into the XPS test chamber, position the test object, set parameters, test the full spectrum of the sample and the narrow spectrum of the target element, and test the element content on the surface of the negative electrode material. When the H content is ≤0.2%, the N content is ≤0.05%, the S content is ≤0.02%, and the O content is ≤0.03%, it is represented by "O"; when any of the above element content conditions are not met, it is represented by "X".
[0070] 3. Test results and analysis
[0071] The test results of this test example are shown in Table 1. Among them, in Examples 1 to 4, different negative electrode precursor materials are used to prepare negative electrode materials. Combined with Comparative Examples 1 to 3, it can be seen that the surface modification method provided by the present application can achieve the purpose of removing the surface groups of the negative electrode material without destroying the structure of the negative electrode material, and further enhance the electrochemical properties of the negative electrode material, thereby enhancing the first-week coulomb efficiency, energy density, and cycle performance of the battery using it. And Comparative Example 1 provides the conventional role of the current aromatic lithium compound-as a pre-lithiation or lithium supplement agent to modify the negative electrode material, so that lithium ions can enter the interior of the negative electrode material, so that the negative electrode material reaches a lithium-rich state. However, the present application reduces the reducing ability of the reagent so that it only plays the role of eliminating the surface groups of the graphite material, and only a small amount of lithium ions enter the interior of the graphite. Therefore, another inventive concept for surface modification of negative electrode materials is provided.
[0072] It can be seen from Examples 1 to 3 that when graphite is used as the negative electrode material, when the aromatic lithium compound in the first reaction solution satisfies M=W×C×γ; (wherein, ), and the specific capacity of graphite satisfies 340mAh / g≤C (C) When ≤355mAh / g, the modification effect is better.
[0073] It can be explained through Examples 4 to 6 that when silicon-carbon material is used as the negative electrode material, when the aromatic lithium compound in the first reaction solution satisfies M=W×C×γ; (wherein, ), and the specific capacity of silicon-carbon material meets 400mAh / g≤ (Si) ≤2000mAh / g, the modification effect is better. In addition, when the volume of the first reaction solution satisfies V (Si) =W×λ, which has a better modification effect.
[0074] It can be seen from the test data of Example 5, Examples 7 to 10 and Comparative Example 4 that different second reaction liquids will also affect the electrochemical properties of the negative electrode material. This may be because there will be aromatic lithium residues on the surface of the negative electrode material precursor after the reduction reaction carried out in step S1. When the second reaction liquid is added for cleaning, the second reaction liquid will react with the residual aromatic lithium to generate free lithium ions; and the free lithium ions will further react with the unreacted solvent molecules to produce a complex reaction, thereby changing the electron cloud structure of the solvent molecules and forming a substance similar to the SEI film on the surface of the negative electrode material precursor. In addition, it can be seen from the test that the second reaction liquid is 2-methyltetrahydrofuran, which has a better effect, but its price is relatively high, which easily leads to increased costs. By matching tetrahydropyran and making the volume ratio of 2-methyltetrahydrofuran to tetrahydropyran 1 to 2:1 to 2, a better effect is achieved.
[0075] Table 1. Test results of this test case
[0076] Group First effect / % Energy density / (Wh / kg) Cycle performance / % Element content Example 1 92.5 183 97.5 O Example 2 92.5 185 97.3 O Example 3 92.4 180 97.6 O Example 4 91.0 300 93.8 O Example 5 90.5 320 92.5 O Example 6 88.1 298 89.1 X Example 7 91.8 318 91.7 O Example 8 91.3 332 93.1 O Example 9 92.0 335 93.1 O Example 10 91.6 319 91.3 X Embodiment 11 91.2 306 90.0 O Comparative Example 1 89.4 310 89.7 X Comparative Example 2 92.0 170 97.0 X Comparative Example 3 85.0 298 88.6 X
[0077] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A negative electrode material, characterized in that: In the negative electrode material, the hydrogen content is not higher than 0.2%, the nitrogen content is not higher than 0.05%, the sulfur content is not higher than 0.02%, and the oxygen content is not higher than 0.03%.
2. A surface modification method for preparing the negative electrode material according to claim 1, characterized in that: The steps include: S1. In an inert gas atmosphere, mixing a negative electrode material precursor with a first reaction liquid to obtain a first reactant; wherein the first reaction liquid comprises an aromatic lithium compound; S2. Washing the first reactant with the second reaction solution, and obtaining a negative electrode material after drying; Wherein, in S1, the amount of the aromatic lithium compound is M mol, the amount of the negative electrode material precursor is W g, the specific capacity of the negative electrode material precursor is C mAh / g, and the amount of the aromatic lithium compound and the negative electrode material precursor satisfies the following relationship: M=W×C×γ; wherein, 3. The surface modification method according to claim 2, characterized in that: The negative electrode material precursor is graphite, and the specific capacity C of the graphite is (C) Meet: 340mAh / g≤C (C) ≤355mAh / g.
4. The surface modification method according to claim 3, characterized in that: In S1, the volume of the first reaction solution is V (C) L, satisfies the following relationship: V (c) =2×W×λ; where 5. The surface modification method according to claim 2, characterized in that: The negative electrode material precursor is a silicon-carbon material, and the specific capacity C (Si) Meet: 400mAh / g≤C (Si) ≤2000mAh / g.
6. The surface modification method according to claim 5, characterized in that: In S1, the volume of the first reaction solution is V (Si) L, satisfies the following relationship: V (Si) =W×λ; where 7. The surface modification method according to claim 2, characterized in that: The first reaction liquid is prepared by mixing aromatic hydrocarbons, a lithium source, and a solvent, wherein the aromatic hydrocarbons include at least one of biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, pyrene, pyrene derivatives, and diphenylmethane.
8. The surface modification method according to claim 2, characterized in that: The second reaction liquid includes at least one of 2-methyltetrahydrofuran, tetrahydropyran, pentahydrofuran, and hexahydrofuran.
9. The surface modification method according to claim 8, characterized in that: The second reaction liquid includes 2-methyltetrahydrofuran and tetrahydropyran; calculated by volume ratio, the 2-methyltetrahydrofuran: the tetrahydropyran=1-2:1-2.
10. A battery, characterized in that: The battery comprises the negative electrode material according to claim 1 or the negative electrode material prepared by the surface modification method according to any one of claims 2 to 9.
Citation Information
Patent Citations
Pre-lithiation method for negative electrode material of lithium-ion battery
CN110010863A
Pre-lithiated negative electrode material as well as preparation method and application thereof
CN111584853A
Industrial production method of lithium alloy film material
CN111785933A
Chemical pre-lithiation method for graphite electrode of lithium ion battery
CN112490394A
Method for pre-lithiation of silicon-based negative electrode material
CN112563457A